Food-borne hazards in a transforming pork value chain in Hanoi: Basis for future risk assessments - Fahrion, Anna S.; Lapar, Ma. Lucila; Nguyen Ngoc Toan; Do Ngoc Thuy; Grace, Delia (2013)
Pork is the most consumed meat in Vietnam. Driven by market liberalization and economic growth, food chains especially in urban areas adapt to convenience lifestyles (e.g., the promotion of refrigeration systems) and move away from the traditional methods of food retail and preparation. Along with these changes, as well the hazards, and consequently risks, from pork are changing. We investigated pork samples sourced from different retail types -traditional to modern- for a selection of typical food-borne hazards in order to compare levels of contamination and safety. We included samples from supermarkets and wet markets in urban Ha Noi, as well as samples from village markets. In addition, taking into account information about hygiene and practices related to handling and preparing pork, we tried to describe probable changes in consumer exposure. In this context, we carry out descriptive hazard characterization and exposure assessment for Enterobacteriaceae including E. coli O157, Listeria monocytogenes and antibiotic residues. This descriptive pilot study points out possible emerging risks to be addressed and supplies data to inform future risk assessments.